Sozialwort des Okumenischen Rates der Kirchen in Osterreich - wzór ekumenicznej współpracy chrześcijan - Podzielny, Janusz (Studia Oecumenica, 2012)
The aim of this article is to present the content of social document, which was published by the Ecumenical Council of Churches in Austria (÷RK÷) in 2003. This Sozialwort is in fact a model of ecumenical cooperation for Christians and may be a kind of ìcompassî inspired by the Word of God, which shows the right way among the many changes and the various challenges existing in the modern world. It seems that, especially in the context of the current economic crisis, which is also a crisis of moral values, social reflections of Austrian Christian Churches (on education, media, social relationships, work and the economy, peace and justice, as well as sustainable development) can be very helpful not only for Christians, but also for all people of good will.